Collaboration Between Subtitling Academics and Practitioners: A Proposal for SubComm - Silvester, Hannah; Tuominen, Tiina (Journal of Audiovisual Translation, 2021)
This article proposes the application of public translation studies put forward by Koskinen (2010) to the field of audiovisual translation (AVT). We argue that AVT scholars and practitioners would benefit from the implementation of a long-term, reciprocal collaboration. This would involve the formation of a community of academics and subtitlers, creating a space for regular dialogic communication that would be mutually beneficial. The article first explores the concept of public translation studies, examining how and why this framework might be useful in AVT. We then present the findings of a scoping questionnaire, in which subtitlers working in the UK and Ireland were surveyed about their interest in collaborating with academics. Respondents indicated an interest in opportunities for professional development, community-building and collaboration. In addition, based on the results we highlight a number of areas around which these activities could be centred, including, for example, opportunities for subtitlers to enhance their practical skill set, to improve their career opportunities and the collective standing of the profession, to discuss translation dilemmas and to inform academia. We end by proposing some concrete next steps for the development of a subtitling community, and the possible role of academics and subtitlers within such an initiative. Lay Summary Working as a subtitler can be challenging in many ways: technological developments such as machine translation are changing the work rapidly, working conditions are sometimes demanding, and the work can be lonely because it is often done on a freelance basis. Therefore, subtitlers could benefit from new ways to work together, share information and advocate for better working conditions. It could also be useful to build closer contacts with researchers who have an interest in subtitling. Contacts with academia would allow practitioners to learn how research might benefit them and to contribute to future projects. This article presents a proposal for forming a community of practitioners and academics. As a first step, we conducted a survey with subtitlers based in the UK and Ireland to find out what topics practitioners would like to discuss with academics. The responses indicate that many practitioners want to enhance their practical skills by learning about topics such as new technology, and they want to network and improve their working conditions. There is also some interest in learning about and contributing to research. Based on these responses, we will conclude the article by introducing a new community of subtitlers and practitioners we are launching: SubComm.